2022
DOI: 10.1177/00915521221125822
|View full text |Cite
|
Sign up to set email alerts
|

Community College International Leaders’ Sensemaking: Entrepreneurial Leadership Skills and Behavior

Abstract: Objective: This article explores entrepreneurial leadership behavior from the vantage point of mid- and senior-level administrators who lead international education initiatives at U.S. community colleges. Administrators’ choices are examined to understand how they develop and use strategies for targeted problem solving within their institutional context. Research questions posed in this study include: (1) How, if at all, do community college international education leaders (CC-IELs) self-identify as entreprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Our work makes a number of important contributions to the literature. First, even though the impact of institutional entrepreneurship and transformational leadership on organizational change has been examined separately, few studies have explored these two factors' influence on organizational change (Brodnik and Brown, 2018;Ma et al, 2020;Raby et al, 2023). Thus, the findings of the present paper contribute to our knowledge about the crucial role that institutional entrepreneurship and transformational leadership play in organizational changes.…”
Section: Theoretical Contributionsmentioning
confidence: 86%
See 1 more Smart Citation
“…Our work makes a number of important contributions to the literature. First, even though the impact of institutional entrepreneurship and transformational leadership on organizational change has been examined separately, few studies have explored these two factors' influence on organizational change (Brodnik and Brown, 2018;Ma et al, 2020;Raby et al, 2023). Thus, the findings of the present paper contribute to our knowledge about the crucial role that institutional entrepreneurship and transformational leadership play in organizational changes.…”
Section: Theoretical Contributionsmentioning
confidence: 86%
“…They observed the crucial part that leadership plays in organizational change, including the changes that go beyond the organizational boundaries, building on the positional power of the organizations initiating the changes. There are studies in the education sector which consider both institutional entrepreneurship and transformational leadership (Ma et al, 2020;Raby et al, 2023), but these two factors are not widely examined in the context of public organizations. Despite this promising research direction that combines transformational leadership and institutional entrepreneurship, which promises to unpack the close relationship between these two factors in explaining organizational change and its diffusion beyond the organizational boundary, there is a scarcity of research in the developing country context.…”
Section: Introductionmentioning
confidence: 99%
“…In this phase, the main theoretical factors that assist outline entrepreneurial leadership in education are discussed and taken collectively. To understand entrepreneurial leadership in education, transformational leadership idea become proposed by way of Raby et al (2023). According to this theory, a pacesetter can encourage and motivate followers to sacrifice their non-public pastimes for the collective good.…”
Section: A Theoretical Framework For Educational Entrepreneurial Lead...mentioning
confidence: 99%
“…In their 2015 study on the establishment of community-led social enterprises, Munoz et al (2015) found that the creation of such rural community-based service providers required both community capacities and entrepreneurial skills. Entrepreneurial leaders, according to Raby et al (2023), exploited traits such as cooperation to create a culture of innovation and strategically employed connections with stakeholders to establish themselves as navigators of institutional environments. Additionally, Nofrida and Mahmudah (2023) demonstrated that the university student's entrepreneurial skills measuring tool has five components, including technopreneur, ecopreneur, sociopreneur, edupreneur, and entrepreneur management; the quality of the tool was well tested using two approaches, namely content and construct validity; practicality in developing the instrument has a very practical value in terms of clarity of instructions, use of the instrument, and other practical aspects.…”
Section: Skills Needed In Entrepreneurshipmentioning
confidence: 99%